232k views
0 votes
Enter the value of n so the expression (-y+ 5.3) + (7.2y-9) is equivalent to 6.2y+n.

User Balzafin
by
5.1k points

1 Answer

2 votes

Answer:


\boxed{\bold{Decimal: \ n \ = \ -3.7}}


\boxed{\bold{Fraction: \ n=-(37)/(10)}}

Step By Step Explanation:

Rewrite Equation:


\bold{\left(-y+5.3\right)+\left(7.2y-9\right)=6.2y+n}

Switch Sides:


\bold{6.2y+n=\left(-y+5.3\right)+7.2y-9}

Remove Parenthesis: (a) = a


\bold{6.2y+n=-y+5.3+7.2y-9}

Group Like Terms:


\bold{6.2y+n=-y+7.2y+5.3-9}

Combine Similar Elements:
\bold{-y+7.2y=6.2y}


\bold{6.2y+n=6.2y+5.3-9}

Subtract:
\bold{5.3-9=-3.7}


\bold{6.2y+n=6.2y-3.7}

Multiply Both Sides By 10:


\bold{6.2y\cdot \:10+n\cdot \:10=6.2y\cdot \:10-3.7\cdot \:10}

Refine:


\bold{62y+10n=62y-37}

Subtract 62y From Both Sides:


\bold{62y+10n-62y=62y-37-62y}

Refine:


\bold{10n=-37}

Divide Both Sides By 10:


\bold{(10n)/(10)=(-37)/(10)}

Simplify:


\bold{n=-(37)/(10)}

Turn Fraction Into Decimal:


\bold{-37 \ / \ 10}

Refine:


\bold{-3.7}

- Mordancy

User Timbo White
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.